MANAJEMEN PRODUKSI PROGRAM SIARAN “SHECANGKIR TEH PAGI” DI SHE RADIO 99,6 FM - Riyanti, Meyliana Eka; Winata, Muhammad Danu (The Commercium, 2024)
This research aims to explore the production management of the "Shecangkir Teh Pagi" program on She Radio 99.6 FM by applying the 6M approach (Man, Money, Material, Machine, Method, and Market) developed by George R. Terry. The advancement of broadcasting technology has transformed the dynamics between radio and its audience, enabling more personal and flexible access. She Radio leverages technology to attract and retain listeners, particularly targeting the housewife segment. Data collection techniques included observation and interviews. The findings indicate that strategies such as technological updates, innovative content development, expansion of off-air activities, enhancement of production team skills, strengthening of digital marketing strategies, and improved evaluation and feedback mechanisms have successfully increased listener loyalty. Direct interaction through social media and other digital platforms has been key in understanding and meeting audience needs. This study concludes that a comprehensive approach integrating technology, audience interaction, and innovative content development is crucial for the success of radio in the digital era.